Wide posterior gluteal‐thigh propeller flap for reconstruction of perineal defects. Issue 2 (8th October 2020) - Ordenana, Carlos; Dalla Pozza, Edoardo; Rampazzo, Antonio; Said, Sayf; McBride, Jennifer; Kessler, Hermann; Bassiri Gharb, Bahar
Abstract: Introduction: With increasing popularity of minimally invasive approaches to abdominoperineal resection (APR), thigh‐based flaps are becoming the preferred option for reconstruction. The gluteal‐thigh flap provides sufficient bulk, albeit with a high complication rate. We reevaluated the vascularization and design of the gluteal‐thigh flap. The purpose of this study is to highlight the importance of the vascularization of the posterior thigh skin by the descending branch of the inferior gluteal artery (IGA) and the profunda femoris artery (PFA) perforators to design a more reliable and versatile gluteal thigh flap. This flap is indicated in selected cases in which use of vertical rectus abdominis musculocutaneous flap is not feasible. Methods: Eleven fresh cadavers were used. The course, distribution, and diameter of IGA and PFA perforators were recorded. A wide posterior gluteal‐thigh propeller flap (WPGTPF) was designed including the distance between the ischiatic tuberosity and greater trochanter; and extending it to within 8 cm of the popliteal fossa to improve flap reliability. Ten patients (mean age of 58.7 ± 10.6 years) underwent APR due to anal cancer (2) and rectal cancer (8); the approach was open in 3, laparoscopic in 6, and robotic in 1. All 10 patients received unilateral flap with a width of 12 ± 3.3 cm and surface of 405.5 ± 175.9 cm 2 . Results: The descending branch of the IGA was dominant in 72.7% of the specimens. In 22.7% of the specimens, the pedicle of the flap derived from the first or second PFA perforators. In one case, there was a double vascularization. Descending branch of the IGA was mapped at 46 ± 7.96 mm on the X ‐axis (horizontal line from the ischial tuberosity [IT] to the greater trochanter) and −12.1 ± 17.9 mm on the Y ‐axis (vertical line from the IT to the Medial Femoral condyle). Its average caliber measured 2.18 ± 0.3 mm. The first and second PFA perforators were located at 101.6 ± 17.9 mm and 104.5 ± 15.5 mm on the X ‐axis; 35.9 ± 27.1 mm and 89.2 ± 37.6 mm on the Y ‐axis. Their average diameters were 1.84 ± 0.41 mm and 1.48 ± 0.3 mm. In two cases, the flap was based on the first PFA perforator, the rest were on the descending branch of the IGA. Neither complete nor partial flap necrosis was observed. One patient developed coccyx osteomyelitis treated and resolved with bone debridement and one patient developed a seroma of the lateral thigh that was treated conservatively. Three patients underwent a debulking procedure by a combination of liposuction and resection to improve the gluteal symmetry. All ten flaps survived completely. Conclusions: Harvest of a wide flap that includes the PFA perforators and implementation of the propeller design increase the survival and versatility of the flap.